Ideological Radicalization Among Adolescents: Multidimensional Analysis and Prevention Strategies - Sarnoto, Ahmad Zain; Hayatina, Lamya; Rahmawati, Sri Tuti (Jurnal Ilmu Pendidikan dan Humaniora, 2024)
Ideological radicalization among adolescents poses significant challenges to societal stability and security, necessitating comprehensive strategies for prevention and intervention. This research conducts a multidimensional analysis to explore the complex interplay of social influences, individual vulnerabilities, and ideological exposure in shaping susceptibility to extremist ideologies among adolescents. Drawing upon empirical findings, theoretical frameworks, and insights from existing literature, the study elucidates key patterns, relationships, and implications for policy, practice, and future research in the field. The analysis reveals the influential role of peer networks in amplifying vulnerability to radicalization, while also highlighting the nuanced dynamics of family influences and individual vulnerabilities. Psychological factors, such as identity crises and trauma, are identified as critical determinants of susceptibility to extremist narratives. Moreover, the proliferation of online radicalization emerges as a significant driver of radicalization processes, underscoring the importance of targeted interventions to address online influences and promote media literacy among adolescents. Policy implications emphasize the need for integrated approaches to prevention, including investments in education, community engagement, and online regulation. Practitioners are encouraged to prioritize community-based interventions and early support services to address underlying drivers of radicalization among at-risk adolescents.